2017
DOI: 10.1001/jamafacial.2016.1105
|View full text |Cite
|
Sign up to set email alerts
|

Classifying and Standardizing Panfacial Trauma With a New Bony Facial Trauma Score

Abstract: IMPORTANCEThe practice of facial trauma surgery would benefit from a useful quantitative scale that measures the extent of injury.OBJECTIVE To develop a facial trauma scale that incorporates only reducible fractures and is able to be reliably communicated to health care professionals. DESIGN AND SETTINGA cadaveric tissue study was conducted from October 1 to 3, 2014. Ten cadaveric heads were subjected to various degrees of facial trauma by dropping a fixed mass onto each head. The heads were then imaged with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…It is possible that information about concomitant soft tissue injury was not accurate in the medical record or that the severity could be high even if there was no soft tissue injury due to blunt trauma. FISS, which is an index that assesses the severity of craniofacial trauma, is a clinically simple but useful indicator that can predict the patients' severity of the injury, economic burden, and hospital length of stay [5]. In line with recent studies, this study found that higher FISS was associated with higher trauma severity and that the predictions could be made with the most optimal sensitivity and specificity when the cutoff is 4 points.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is possible that information about concomitant soft tissue injury was not accurate in the medical record or that the severity could be high even if there was no soft tissue injury due to blunt trauma. FISS, which is an index that assesses the severity of craniofacial trauma, is a clinically simple but useful indicator that can predict the patients' severity of the injury, economic burden, and hospital length of stay [5]. In line with recent studies, this study found that higher FISS was associated with higher trauma severity and that the predictions could be made with the most optimal sensitivity and specificity when the cutoff is 4 points.…”
Section: Discussionsupporting
confidence: 80%
“…Another method to assess the severity of facial trauma is facial injury severity scale (FISS) ( Table 1). FISS is a clinically useful index because it can predict the severity of facial injuries and is an indicator of the hospital length of stay [5].…”
Section: Archives Of Craniofacial Surgerymentioning
confidence: 99%
“…To simulate blunt force trauma to the face, an impactor that applied a measurable amount of force was used to create facial fractures. At the University of Virginia, a drop tower was used to drop a 34-kg sled onto the head from heights ranging from 113 cm to 258 cm, generating varying amounts of force delivered to the face ranging from 1340 to 7160 N. 3 Plain radiographic films were used to confirm the presence of fractures, and each head then underwent scanning with high-resolution computed tomography (CT) ( Figure 1A and B). A similar protocol was used at The Ohio State University Wexner Medical Center; however, the impactor was hydraulically powered to deliver a similar range of force.…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 4 5 ] According to the literature, men are more often affected, and the male-to-female ratio is about 2:1–8.9:1. [ 3 6 7 8 9 ] Young men are most often affected. In the age group between 15 and 29 years, jaw injuries are most frequently detected.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 16 17 18 19 ] Neither the AO papers nor other authors use the nomenclature for “panfacial fractures” or “complex fractures” consistently. [ 4 7 19 20 21 ] According to the definition applied in our study, a panfacial fracture includes several fractures from different facial regions. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%